Henry Kissinger a diplomat's life. - Cox, Mary Ellen (New York A & E Television Networks, 1995)
"Henry Kissinger is one of the world's most noted statesmen. As Secretary of State under Richard Nixon, he carved out a reputation for shrewd diplomacy, and became an international power broker of the first magnitude ... The personal story of the boy who fled Nazi Germany and arrived penniless in the United States is told by his mother and son. The tireless, behind-the-scenes schemer is recalled by Nixon associates John Ehrlichman and Alexander Haig."--Container
With 1 converted disc.
Executive producer, Liza Zeff ; A & E director, documentary programming, Bill harris ; A & E executive producer, Michael Cascio.
Narrator, Barry Serafin.
VHS format.
In English.
Keywords: Kissinger, Henry -- 1923-.; Statesmen -- United States -- Biography